Wind power characterization in the Lages city - SC, Brazil - Soccol,Olívio José (2010)
The main objective of this work was to determinate the nominal wind and the wind power, based on mathematical adjustments in the Lages city, SC-Brazil. The study used data comprising the period between 1976 and 2006. The wind average velocity was osted by Lages Meteorological Station located at 27º49'S, 50º12' W, and 937 meters of altitude. For the estimated wind temporal distribution, a methodology based on wind velocity curves was used. The nominal velocity that made wind power maximum in Lages was 10.33 km h-1 77 days long. This velocity provides an average wind power 16.6 W m-2 annually. The results showed that wind power cow be characterized as a simple alternative to be used in agriculture.